Treatment Outcomes for Military Veterans With Posttraumatic Stress Disorder: Response Trajectories by Symptom Cluster. Issue 3 (29th June 2018) - Phelps, Andrea J.; Steele, Zachary; Cowlishaw, Sean; Metcalf, Olivia; Alkemade, Nathan; Elliott, Peter; O'Donnell, Meaghan; Redston, Suzy; Kerr, Katelyn; Howard, Alexandra; Nursey, Jane; Cooper, John; et al.
Abstract: Although effective posttraumatic stress disorder (PTSD) treatments are available, outcomes for veterans with PTSD are relatively modest. Previous researchers have identified subgroups of veterans with different response trajectories but have not investigated whether PTSD symptom clusters (based on a four‐factor model) have different patterns of response to treatment. The importance of this lies in the potential to increase treatment focus on less responsive symptoms. We investigated treatment outcomes by symptom cluster for 2, 685 Australian veterans with PTSD. We used Posttraumatic Stress Disorder Checklist scores obtained at treatment intake, posttreatment, and 3‐ and 9‐month follow‐ups to define change across symptom clusters. Repeated measures effect sizes indicated that arousal and numbing symptoms exhibited the largest changes between intake and posttreatment, d RM = −0.61 and d RM = −0.52, respectively, whereas avoidance and intrusion symptoms showed more modest reductions, d RM = −0.36 and d RM = −0.30, respectively. However, unlike the other symptom clusters, the intrusions cluster continued to show significant changes between posttreatment and 3‐month follow‐up, d RM = −0.21. Intrusion and arousal symptoms also showed continued changes between 3‐ and 9‐month follow‐ups although these effects were very small, d RM = −0.09. Growth curve model analyses produced consistent findings and indicated modest initial changes in intrusion symptoms that continued posttreatment. These findings may reflect the longer time required for emotional processing, relative to behavioral changes in avoidance, numbing, and arousal, during the program; they also reinforce the importance of prioritizing individual trauma‐focused therapy directly targeting intrusions as the core component of programmatic treatment.